Follicular deviation and acquisition of ovulatory capacity in bovine follicles - Sartori, R.; Fricke, P. M.; Ferreira, JCP; Ginther, O. J.; Wiltbank, M. C. (Soc Study Reproduction, 2001)
Selection of dominant follicles in cattle is associated with a deviation in growth rate between the dominant and largest subordinate follicle of a wave (diameter deviation). To determine whether acquisition of ovulatory capacity is temporally associated with diameter deviation, cows were challenged with purified LH at known times after a GnRH-induced LH surge (experiment 1) or at known follicular diameters (experiments 2 and 3). A 4-mg dose of LH induced ovulation in all cows when the largest follicle was greater than or equal to 12 mm (16 of 16), in 17% (1 of 6) when it was 11 mm, and no ovulation when it was less than or equal to 10 mm (0 of 19). To determine the effect of LH dose on ovulatory capacity, follicular dynamics were monitored every 12 h, and cows received either 4 or 24 mg of LH when the largest follicle first achieved 10 mm in diameter (experiment 2). The proportion of cows ovulating was greater (P < 0.05) for the 24-mg (9 of 13; 69.2%) compared with the 4-mg (1 of 13; 7.7%) LH dose. To determine the effect of a higher LH dose on follicles near diameter deviation, follicular dynamics were monitored every 8 h, and cows received 40 mg of LH when the largest follicle first achieved 7.0, 8.5, or 10.0 mm (experiment 3). No cows with a follicle of 7 mm (0 of 9) or 8.5 mm (0 of 9) ovulated, compared with 80% (8 of 10) of cows with 10-mm follicles. Thus, follicles acquired ovulatory capacity at about 10 mm, corresponding to about 1 day after the start of follicular deviation, but they required a greater LH dose to induce ovulation compared with larger follicles. We speculate that acquisition of ovulatory capacity may involve an increased expression of LH receptors on granulosa cells of the dominant follicle and that this change may also be important for further growth of the dominant follicle.
Keywords: follicular development; granulosa cells; luteinizing hormone; ovary; ovulation